1993
DOI: 10.1063/1.353804
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal elastic constants of tellurite glasses

Abstract: The aim of the present work is to attempt to make a number of different glasses, based on tellurite as the principal former, which contain substantial quantities of zinc oxide up to 40 mol % ZnO. To study the longitudinal elastic properties, measurements have been made of the velocity of the longitudinal ultrasonic waves propagated through the prepared glasses. The results indicate that the longitudinal elastic constants depend strongly upon the composition of the prepared glasses. A detailed qualitative inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(21 citation statements)
references
References 9 publications
2
17
2
Order By: Relevance
“…El Mallawany [23] summarized data on the refractive index, n, and densities, r, of some tellurite glasses. He attributed the higher values of refractive indices due to the higher values of the density [i.e.…”
Section: Density and Optical Propertiesmentioning
confidence: 99%
“…El Mallawany [23] summarized data on the refractive index, n, and densities, r, of some tellurite glasses. He attributed the higher values of refractive indices due to the higher values of the density [i.e.…”
Section: Density and Optical Propertiesmentioning
confidence: 99%
“…Previous studies focused on the mechanical properties of binary zinc tellurite glasses (100-x)TeO 2 -xZnO allowed evidencing that zinc oxide participates in the glass network and contributes in the increase in glass rigidity [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic longitudinal and shear velocity measurements can be very important tools to investigate elastic property of glasses as ultrasonic velocity is related to elastic moduli whose changes can be associated, among others, to microstructural differences [13,[41][42][43], structural stability [44][45][46][47], formation of glass network [13,17,48,49] and rigidity [14]. In binary TeO 2 -ZnO glass system increase in ZnO resulted in higher network rigidity and subsequently increase in longitudinal modulus [17,50] while in (100−x)TeO 2 -(x)Nb 2 O5 glass an increase in longitudinal velocity was observed with increase in Nb 2 O 5 [51]. Although several elastic studies have been reported for ternary tellurite glasses such as TeO 2 - [14], TeO 2 -WO 3 -PbO [41,47], [54], and (TeO 2 ) 50 -(V 2 O 5 ) 50−x (TiO 2 ) x [55], to our knowledge ultrasonic measurements on TeO 2 -Nb 2 O 5 -ZnO system has not been reported.…”
Section: Introductionmentioning
confidence: 99%